2021
DOI: 10.1007/s10608-021-10231-7
|View full text |Cite
|
Sign up to set email alerts
|

Social Distancing During A COVID-19 Lockdown Contributes to The Maintenance of Social Anxiety: A Natural Experiment

Abstract: Background The COVID-19 pandemic has led to extensive social distancing measures. For those suffering from social anxiety, social distancing coincides with a tendency to avoid social interactions. We used this natural experiment imposed by a COVID-19 lockdown to examine how mandated low social exposure influenced socially anxious university students, and compared their anxiety to that of socially anxious students in preceding academic years with no social distancing. Methods Ninety-nine socially anxious studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 43 publications
1
18
0
3
Order By: Relevance
“…Specifically, levels of social anxiety increased fastest where restrictions were easing fastest. This is consistent with features of social anxiety symptoms where lack of social exposure can maintain symptom severity ( 27 , 28 ). The effect of social restriction severity on depressive symptoms was also examined, and our findings showed that changes in social restrictions did not influence the rate at which people reduced on depressive symptoms.…”
Section: Discussionsupporting
confidence: 84%
“…Specifically, levels of social anxiety increased fastest where restrictions were easing fastest. This is consistent with features of social anxiety symptoms where lack of social exposure can maintain symptom severity ( 27 , 28 ). The effect of social restriction severity on depressive symptoms was also examined, and our findings showed that changes in social restrictions did not influence the rate at which people reduced on depressive symptoms.…”
Section: Discussionsupporting
confidence: 84%
“…Social restriction implemented as the quarantine measure during the COVID-19 pandemic and the perceived social isolation [ 51 ] has contributed to significant psychological distress [ 52 ]. The COVID-19 pandemic affected different aspects of daily life and mental well-being, making it difficult to reduce its influence on a single factor such as social avoidance [ 53 , 54 ]. It was found that social avoidance is a social risk of youth development [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of the course of the disorder in patients diagnosed with social phobia during the pandemic significantly worsened. In experimental studies of students by Arad et al (2021) in the academic year 2019-2020, the level of social anxiety in the respondents remained at a high and unchanged level. They also found that the severity of social anxiety among students was lower before the pandemic period.…”
Section: Phobic Disorders In the Covid-19 Pandemicmentioning
confidence: 93%
“…A study by Saint and Moscovitch (2021) found that wearing masks by people diagnosed with social anxiety can make respondents worry that they will not be well understood. According to the researchers, the impact of wearing masks on the incidence and severity of social anxiety will probably be clear and clinically significant [8,9].…”
Section: Phobic Disorders In the Covid-19 Pandemicmentioning
confidence: 99%